The effect of combined timolol maleat and p/locarpine acetazolamide on the decrease of intraocular pressure in the treatment of primary glaucoma - Sutrisno, Sutrisno (Universitas Gadjah Mada, 1997)
The study was aimed to compare the effects of combination of timolol maleat 0.5% and pilocarpine 2% to acetazolamide 250mg in the treatment of a primary glaucoma. We studied 13 patients with open angle glaucomas and 11 patients with closed angle glaucomas. This study was carried out in a randomized double blind clinical trial. The patients were divided into two groups, A and B. Group A consisted of patients treated with 250 mg acetazolamide t.i.d. and the group B was treated with combination of 0.5% timolol maleat b.i.d. and 2 % pilocarpine q.i.d. This one-day treatment was stopped and seven days later the treatment was interchanged between the two groups. The intraocular pressures were measured just before and two hours after the treatment. The mean decrease of 10P in group A was 17.042 ÃÂ± 14.212mmHg and that of group B was 17.873 ÃÂ± 9.005 mmHg. There was statistically no significant difference (p=0.804) between two groups. The mean decrease of 10P in primary open angle glaucoma in group A was 8.685 ÃÂ± 6.389 mmHg and that of group B was 15.054 ÃÂ± 5.994 mmHg. Statistically there was significant difference (p = 0.014). The mean decrease of 10P In primary closed angle glaucoma in group A was 26.918 ÃÂ± 14.748mmHg and that of group B was 21.205 ÃÂ± 10.993 mmHg. Statistically there was no significant difference (p = 0.3162). In conclusion, there was no significant difference between the use of acetazolamide 250mg q.i.d. the combination of timolol maleat 0.5% b.i.d. and pilocarpine 2% q.i.d. in reducing the 10P of primary glaucoma.Key words: primary glaucoma - lop decrease - acetazolamide - timolol maleat - pilocarpine.